1997
DOI: 10.1021/jp970229+
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of α-Functionalized Terthiophenes on Gold

Abstract: α-Functionalized terthiophenes containing disulfide (−S−T3−H)2 and alkanethiol (HS−(CH2)11−T3−H) anchoring groups have been synthesized for direct immobilization onto gold. Monolayer structures of these compounds are prepared by spontaneous assembly from ethanol solutions on evaporated gold substrates and thoroughly characterized by ellipsometry, contact angle goniometry, infrared and X-ray photoelectron spectroscopy, and cyclic voltammetry. The two molecules coordinate to the gold substrate exclusively via th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
86
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(95 citation statements)
references
References 75 publications
9
86
0
Order By: Relevance
“…30,31 Moreover, the positions of these two peaks are in accordance with earlier reported values for thiophene. 24,32,33 The S 2s signature appears at a binding energy of 228.5 eV (Figure 4d) characteristic also of the aromatic ring. 34,35 Globally, the atomic ratios deduced from these XPS results together with some IR observations (total loss of the initial ester stretch, weak intensity of the ketone band) indicate that the conversion of 1 into 2 is higher than 80% at least.…”
Section: Resultsmentioning
confidence: 99%
“…30,31 Moreover, the positions of these two peaks are in accordance with earlier reported values for thiophene. 24,32,33 The S 2s signature appears at a binding energy of 228.5 eV (Figure 4d) characteristic also of the aromatic ring. 34,35 Globally, the atomic ratios deduced from these XPS results together with some IR observations (total loss of the initial ester stretch, weak intensity of the ketone band) indicate that the conversion of 1 into 2 is higher than 80% at least.…”
Section: Resultsmentioning
confidence: 99%
“…The most important fact is that the carboxyhexyl heads form a layer on the ITO surface which is packed loosely enough that redox processes at the tails are not prevented. As a matter of fact it has been found that in the previously mentioned 29) undecylthiolterthiophene 10 a very close packing blocks the electroactivity of the tails.…”
Section: Carboxyl-terminated Oligothiophenesmentioning
confidence: 90%
“…Compounds 10 and 11, containing an alkanethiol and a disulfide moiety respectively as anchoring groups, have been synthesised for direct immobilisation onto gold 29) . Both molecules were found to coordinate to the gold substrate exclusively via the S1H and S1S groups to yield gold-thiolate bonds.…”
Section: Thiols Disulfides and Alkylsilanesmentioning
confidence: 99%
“…The alkylation gave 52-58% of the desired alkyl-substituted thiophene 2 with a terminal bromide group (Scheme 2.a). In recent studies [19,20], similar alkyl-derivatized thiophenes were obtained by a two or even four step procedure that involved the acylation of the thiophene moiety and the subsequent reduction of the obtained ketone with BH 3 or N 2 H 4 (the latter requiring temporary replacement of the bromide with a hydroquinone ether). The alkylated thiophene derivative was then brominated in the free α-position using N-bromosuccinimide (NBS) in a mixture of acetic acid and chloroform [21] at room temperature and gave the regioselectively brominated thiophene derivative 3 (84-92% yield).…”
mentioning
confidence: 99%